Perspektif Shareholding Versus Stakeholding di Dalam Memahami Fenomena Corporate Governance - Niki Lukviarman (Jurnal Siasat Bisnis, 2005)
This paper challenges the notion of “universalist” or “one-size-fits-all” approach to corporate govern¬ance. It considers different perspective of understanding organization (corporations) which in turn generate alter¬nate paradigms concerning the issue of corporate governance and the way one could govern the corporation. It looks more closely of various assumptions and theoretical frameworks underpinning the governance concepts. The main proposition of this paper is that different perspectives in theory and paradigms result in different diagno¬ses of and the solutions to the problems of corporate governance in practice. Hence, it might be argued that there should be varies model of governance that should be considered based on specific characteristics of organization -and of different context- in order for such model to be effective.Keywords: shareholding, stakeholding, corporate governance, shareholder rights, corporate efficiency